The population genetic structure of Biomphalaria choanomphala in Lake Victoria, East Africa: implications for schistosomiasis transmission - Standley, Claire J.; Goodacre, Sara L.; Wade, Christopher M.; Stothard, J. Russell (BioMed Central, 2014)
Background: The freshwater snail Biomphalaria acts as the intermediate host of Schistosoma mansoni, a globally important human parasite. Understanding the population structure of intermediate host species can elucidate transmission dynamics and assist in developing appropriate control methods. Methods: We examined levels of population genetic structure and diversity in 29 populations of Biomphalaria choanomphala collected around the shoreline of Lake Victoria in Uganda, Kenya and Tanzania, where S. mansoni is hyper-endemic. Molecular markers were utilized to estimate the degree to which snail populations are genetically differentiated from one another. Results: High levels of snail genetic diversity were found coupled with evidence of geographically-determined population structure but low levels of local inbreeding. The data are consistent with an effect of schistosome infection on population structure of intermediate host snails, but other factors, such as habitat and historical demographic changes, could also be important determinants of the degree of population genetic structure in Biomphalaria choanomphala. Conclusions: The low stratification of populations and high genetic diversity indicates potentially less local compatibility with intermediate snail populations than previously theorized, and highlights the importance of coordinated parasite control strategies across the region.